Analisis Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Restoran di Kota Medan (Studi kasus: Badan Pengelola Pajak dan Retribusi Daerah Kota Medan) - Natasya Hikma Matondang; Effendi Sadly; Faty Rahmarisa (Universitas Islam Sumatera Utara, 2022)
Restaurant Tax is a tax on services provided by restaurants. Restaurant Tax managed by the Regional Tax and Retribution Management Agency (BPPRD) of Medan City is a Regional Tax that can have a positive impact on increasing Regional Original Income (PAD) because there are more restaurants in the area. Medan city. The research method uses the Quantitative Analysis method, using this method to analyze the data for comparison to the results of calculations research. The results can be seen that the rate of increase in the growth of the restaurant business in Medan City which is registered with the Medan City Regional Tax and Retribution Manager from 2011 to 2020 is quite volatile, where the influence of Taxpayers, Per capita Income, Population has a positive effect on Medan City Restaurant Tax receipts